UNDERSTANDING THE CONCEPT OF EDUCATION FOR 2020/2021 UNDERGRADUATE STUDENTS, DEPARTMENT OF GUIDANCE AND COUNSELING, FIP, MANADO STATE UNIVERSITY - Deklay Nainggolan (Prodi Bimbingan Konseling Universitas Negeri Manado, 2020)
This study aimed to determine the level of understanding of the FIP Unima undergraduate counseling (BK) students about the concept of education. This research was conducted using a descriptive method, by taking a sample of 44 students of BK, FIP Unima in their first semester (the academic year 2020/2021). Data were collected through interviews and tests. The descriptive analysis techniques were used. The results showed that the understanding of the concept of education for undergraduate students of BK FIP Unima was generally satisfactory. This can be seen from 79% of undergraduate students of BK FIP Unima were understand the concept of education and 21% of students didn’t. The results showed there was a misunderstanding of the Principles of Education and Designing future school models, especially in the concept of Lifelong Education and Curriculum Models for schools.